The regenerative response of cardiac interstitial cells. (22nd October 2022) - Rolland, Laura; Harrington, Alenca; Faucherre, Adèle; Abaroa, Jourdano Mancilla; Gangatharan, Girisaran; Gamba, Laurent; Severac, Dany; Pratlong, Marine; Moore-Morris, Thomas; Jopling, Chris
ABSTRACT: Understanding how certain animals are capable of regenerating their hearts will provide much needed insights into how this process can be induced in humans in order to reverse the damage caused by myocardial infarction. Currently, it is becoming increasingly evident that cardiac interstitial cells play crucial roles during cardiac regeneration. To understand how interstitial cells behave during this process, we performed single-cell RNA sequencing of regenerating zebrafish hearts. Using a combination of immunohistochemistry, chemical inhibition, and novel transgenic animals, we were able to investigate the role of cell type-specific mechanisms during cardiac regeneration. This approach allowed us to identify a number of important regenerative processes within the interstitial cell populations. Here, we provide detailed insight into how interstitial cells behave during cardiac regeneration, which will serve to increase our understanding of how this process could eventually be induced in humans.